Robert Whelan-Joseph Kirwan-Paul Haffner, The Cross and the Rain Forest. A Critique of Radical Green Spirituality. Acton Institute for the Study of Religion and Liberty, William B. Eerdmans Publ. Co. Grand Rapids, Michigan, 1996. ISBN 0-80284201- 1. 163 páginas - Crespo, Ricardo F. (1998)
Fil: Crespo, Ricardo F. Universidad Austral; Argentina